2021
DOI: 10.3389/fmolb.2021.611367
|View full text |Cite|
|
Sign up to set email alerts
|

A Nanomule Peptide Carrier Delivers siRNA Across the Intact Blood-Brain Barrier to Attenuate Ischemic Stroke

Abstract: The blood-brain barrier (BBB) hinders the distribution of therapeutics intended for treatment of neuroinflammation (NI) of the central nervous system. A twelve-amino acid peptide that transcytoses the BBB, termed MTfp, was chemically conjugated to siRNA to create a novel peptide-oligonucleotide conjugate (POC), directed to downregulate NOX4, a gene thought responsible for oxidative stress in ischemic stroke. The MTfp-NOX4 POC has the ability to cross the intact BBB and knockdown NOX4 expression in the brain. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Another BBB-crossing siRNA technology, the XB 3 platform developed by Bioasis works via peptide conjugation (a 12 amino acid peptide called MTfp) and receptor-mediated transcytosis. Proof-of-concept has been obtained for the silencing of NOX4 which plays a role in ischaemic stroke [ 111 ]. After induction of ischaemic stroke, animals treated with this novel siRNA suffered significantly reduced infarcts and improved recovery [ 111 ].…”
Section: Targeting Nucleic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Another BBB-crossing siRNA technology, the XB 3 platform developed by Bioasis works via peptide conjugation (a 12 amino acid peptide called MTfp) and receptor-mediated transcytosis. Proof-of-concept has been obtained for the silencing of NOX4 which plays a role in ischaemic stroke [ 111 ]. After induction of ischaemic stroke, animals treated with this novel siRNA suffered significantly reduced infarcts and improved recovery [ 111 ].…”
Section: Targeting Nucleic Acidmentioning
confidence: 99%
“…Proof-of-concept has been obtained for the silencing of NOX4 which plays a role in ischaemic stroke [ 111 ]. After induction of ischaemic stroke, animals treated with this novel siRNA suffered significantly reduced infarcts and improved recovery [ 111 ].…”
Section: Targeting Nucleic Acidmentioning
confidence: 99%
“…17 In addition, MTfp effectively delivered NOX4-specific small interfering RNA (siRNA) to the brain, reducing ischemic stroke. 18 These studies indicate that MTfp, as a brain-targeting peptide, has the potential to facilitate drug delivery to the brain.…”
Section: Introductionmentioning
confidence: 98%
“…It could be a feasible way to reduce the expression of NOX4 by using NOX4-specific siRNA. It has been demonstrated that a twelve-amino acid peptide (MTfp), derived from melanotransferrin (MTf), could efficiently transport siRNA through the BBB model by forming a novel peptide-oligonucleotide conjugate (POC) [ 106 , 107 ]. MTfp-NOX4 POC further reduced the expression level of NOX4.…”
Section: Therapy For Ischemic Strokementioning
confidence: 99%